Avian Influenza Risk Environment: Live Bird Commodity Chains in Chattogram, Bangladesh - Høg, Erling; Fournié, Guillaume; Hoque, Md. Ahasanul; Mahmud, Rashed; Pfeiffer, Dirk U.; Barnett, Tony (Frontiers in Veterinary Science, 2021)
In this paper, we identify behaviours in live bird commodity chains in Chattogram, Bangladesh, which may influence the risk of pathogen emergence and transmission: the nature of poultry trade, value appropriation and selling sick or infected birds. Examining the reasons why actors engage in these behaviours, we emphasize the politics of constraints within a context of real-world decisions, governed by existential and pragmatic agency. Focusing on contact zones and entanglement, analysing price volatility, patron-client relationships and behaviours of last resort, we argue that agency and structure specific to the Bangladeshi context produce a risk environment. Structural constraints may reinforce risky occupational practices and limit individual agency. Structural constraints need to be addressed in order to tackle animal and zoonotic disease risk along live animal commodity chains.